Third-generation CDMA systems for enhanced data services - Mandyam, Giridhar; Lai, Jersey (Amsterdam ; Boston : Academic Press, 2002)
The use of mobile communication devices has grown phenomenally throughout the world during the last few years. With strong consumer demand to increase data delivery (large emails, browsing the Internet on wireless devices, transferring video images, etc.), engineers are faced with the challenge of enhancing CDMA to provide larger data capabilities while improving voice signals for clearer reception. In November 2001 the U.S. Federal Communications Commission released a much broader band of frequencies to wireless service providers, which will speed up the development of these systems. Simulation results demonstrate the performance benefits of the proposed systems versus their third-generation predecessors Up-to-date overview of the standardised air interface.
Preface -- 1. Introduction to Cellular Systems -- 2. Direct-Sequence Spread Spectrum Systems -- 3. The Mobile Channel and Diversity Reception in CDMA Systems -- 4. An Overview of IS-95 and cdma2000 -- 5. 1X-EV: Evolution of cdma2000 -- 6. WCDMA Overview -- 7. IS-95, cdma2000, 1X-EV, and WCDMA Performance -- 8. Handover in IS-95, cdma2000, 1X-EV, and WCDM -- Appendix: CDMA Transceivers -- Author Biographies -- Index.
Includes bibliographical references and index.
Keywords: Code division multiple access; Electronic books